Sustainable regionalism: Reading the sustainability approach in the context of regionalist architecture - Elahe Zoghi Hosseini; Darab Diba; Hamed kamelnia; Mostafa Mokhtabad Ameri (تحقیقات کاربردی علوم جغرافیایی)
The innate sense of interaction with the region is a sign of environmental sensitivity, which is very vital in the 21st century. Today, it is inevitable that regionalism should be included in a larger discourse of architecture, and that the debate over the role of the use of regional green architecture as a factor in cultural identity and sense of place should be promoted. The present study argues that regionalist architecture has entered a new phase of its evolutionary process, which is sustainable regionalism. In this view, regions must be defined in terms of their unique resources and specific constraints. Instead of being influenced by globalization, regions must follow a complex interdependence in a global and regional interaction system that is physical, social, cultural, and most importantly ecological. Therefore, using the method of qualitative content analysis based on the logic of inductive reasoning, from the textual data and architectural experiences mentioned in the research, move and by extracting the hidden concepts in it, gradually reach more abstract levels of sustainable regionalism. We will find. In addition, using the latest works of architecture selected by international institutions and awards and competitions, we are developing examples of sustainable regionalism. Achieving a model or theoretical framework that demonstrates latent disciplines and repetitive patterns in regionalist architecture and sustainable architecture can be the culmination of research.